2018
DOI: 10.1080/10790268.2017.1422881
|View full text |Cite
|
Sign up to set email alerts
|

At-home genital nerve stimulation for individuals with SCI and neurogenic detrusor overactivity: A pilot feasibility study

Abstract: Short term at-home GNS reduced urinary incontinence and helped subjects meet their bladder management goals. These data inform the design of a long-term clinical trial testing of GNS as an approach to reduce NDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Goldman et al used coiled wire to stimulate the DGN in 21 women with OAB and reported that 76% of the patients experienced a 50% reduction in pad weight and 47% a 50% reduction in incontinence episodes . DGN stimulation via transcutaneous electrodes on NDO has also shown promising outcomes . However, the sample sizes in these studies were small.…”
Section: Treatments Under Researchmentioning
confidence: 99%
“…Goldman et al used coiled wire to stimulate the DGN in 21 women with OAB and reported that 76% of the patients experienced a 50% reduction in pad weight and 47% a 50% reduction in incontinence episodes . DGN stimulation via transcutaneous electrodes on NDO has also shown promising outcomes . However, the sample sizes in these studies were small.…”
Section: Treatments Under Researchmentioning
confidence: 99%
“…Following SCI a majority of people have at least partially preserved bladder sensation, and many use this sensation in their existing bladder management strategy [7]. It is therefore not surprising that positive results have been reported in the small number of pilot studies trialling on-demand DGNS [8][9][10][11]. However, issues remain with the assessment of the suitability of residual sensation and also in the accessibility of stimulation triggers to allow fast application of DGNS [12,13].…”
Section: Specificallymentioning
confidence: 99%
“…For those without residual sensation, in the absence of a physiological trigger for conditional stimulation, the options are continuous or intermittent stimulation. Continuous stimulation has been shown to be effective during standard cystometry [2] and in a limited number of patients (4) over longer periods (between 4 and 8 weeks) [8,14]. Intermittent DGNS has been shown to be effective in one standard cystometry study of 5 SCI participants where a 5 seconds on, 5 seconds off regime was trialled during slow (10 ml/min) fill cystometry, increased the maximum capacity by 120 ml, comparable to a 135 ml increase seen during continuous DGNS [15].…”
Section: Specificallymentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 23 incomplete SCI subjects found DGNS to be tolerable and effective (Brose et al, 2018), showing DGNS may be applicable across a broad range of SCI patients. DGNS has been applied with success as a home based intervention in short pilot studies, reducing incontinence episodes and increasing voided volumes (Lee and Creasey, 2002;Lee et al, 2012;Bourbeau et al, 2018b). This success is tempered by problems found with chronic use of available surface electrodes, particularly with female users, and the lack of an effective trigger to "close the loop" in a conditional neuromodulation system for those with no pelvic sensation (Martens et al, 2010;Lee et al, 2012).…”
Section: Dgns Effectsmentioning
confidence: 99%